Proton field-cycling nucler magnetic resonance relaxometry in the smectic A mesophase of thermotropic cyanobiphenyls: Effects of sonication - Bonetto, Fernando Jose (2004)
Field-cycling nuclear magnetic resonance (NMR) relaxometry was used to study the spin-lattice relaxation dispersion of selected standard smectic A liquid crystals at different temperatures. Relaxation features at both, in presence and absence of a monochromatic ultrasonic field were considered. We show that the laboratory-frame spin-lattice relaxation time is mainly governed by traslational diffusion. Order director fluctuations (ODF) are less important while rotational difussion seems to be only relevant near the clearing point. We show that sonication enhances the ODF contribution in the SmAmesophase, thus enabling the evaluation of different features associated with this mechanism.